2020
DOI: 10.5114/ait.2020.95020
|View full text |Cite
|
Sign up to set email alerts
|

The role of clinical pharmacology in enhanced recovery after surgery protocols: a comprehensive review

Abstract: Clinical pharmacology has changed many clinical systems, including anaesthesia delivery in both the hospital and ambulatory surgery settings. Ambulatory surgery centres, also known as outpatient care centres, are facilities that provide same-day healthcare services to patients, which are costeffective and convenient. These facilities can offer surgical care, intervention, and diagnostic and preventative procedures (Figure 1). Ambulatory surgery centres may choose to perform procedures in one specific specialty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Therefore, the enhanced recovery after surgery (ERAS) protocol has been established to increase patient's well-being after surgery. One of the important aspects of ERAS is rational fluid and food restriction prior to anesthesia (Borys et al 2020;Kaye et al 2020;Taniguchi et al 2012). Both ERAS and the European Society for Clinical Nutrition and Metabolism (ESPEN) guidelines recommend oral intake of a carbohydrate-rich drink prior to surgery (Nygren et al 2013;Weimann et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the enhanced recovery after surgery (ERAS) protocol has been established to increase patient's well-being after surgery. One of the important aspects of ERAS is rational fluid and food restriction prior to anesthesia (Borys et al 2020;Kaye et al 2020;Taniguchi et al 2012). Both ERAS and the European Society for Clinical Nutrition and Metabolism (ESPEN) guidelines recommend oral intake of a carbohydrate-rich drink prior to surgery (Nygren et al 2013;Weimann et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, early mobilization reduces the risk of postoperative deep venous thrombosis and facilitates a faster return to daily routines by allowing an earlier restoration of both the bladder and bowel function 45 . The aforementioned parameters are compatible with the Enhanced Recovery After Surgery (ERAS) protocols that have been recently adopted by many institutions which have been related with favorable outcomes regarding patients' recovery 46 . A critical point for ERAS protocols is the reduction of opioid consumption which is achieved by using local anesthetics and nerve blocks 46 .…”
Section: Discussionmentioning
confidence: 93%
“…46 A critical point for ERAS protocols is the reduction of opioid consumption which is achieved by using local anesthetics and nerve blocks. 46 To that end, Athanasiou et al reported that the proportion of patients who consumed opioids under LA was significantly lower compared to those in RA group (p = .002).…”
Section: Comparative Studies/meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, all patients were anaesthetized with the same anaesthetics. No premedication with anxiolytics was administered prior to surgery since avoiding these drugs is common clinical practice [22].…”
Section: Discussionmentioning
confidence: 99%